DIVESTASI SEBAGAI ALTERNATIF MEMPERTAHANKAN VIABILITAS PEREKONOMIAN INDONESIA (DARI PERSPEKTIF ECONOMIC ANALYSIS OF LAW) - Tanaya, Putu Edgar (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
This study aims to find out developments and constraints implementation of the divestitures in Indonesia, both conducted by STATE-OWNED ENTERPRISES as well as foreign investor. Understanding of the developments and constraints will make it easier to steps that must be performed related constraints â obstacles occur. One of the problems that arise related divestitures are not yet the existence of a clear and definite criteria concerning the areas that must be controlled by the State.Article 33 of the Constitution states the relating fields with his life many people should be controlled by the State. Setting the article expressly and clearly gives the criteria field of the divestment. Based on the study of laws and decision the Constitutional Court there are several fields relating to: electrical fields, defense and security fields, the fields of water resources.